Educational branding in private spanish universities: building brands that the public fall in love with - Casanoves-Boix, Javier; Küster-Boluda, Inés; Vila-López, Natalia (Journal of Management and Business Education, 2020)
This research was carried out to examine the role of university brand capital in private Spanish universities. To this end, an empirical study was carried out with a quantitative sample of 993 valid responses from the different agents involved (343 lecturers, 164 service staff, and 486 students). The results obtained show the impact of each of the variables of brand capital at the educational level and, in particular, the importance of building brand image to maximize the perception of brand capital in private Spanish universities. At the same time, there are significant differences in perception among the different university agents involved, the service staff having the highest average in all the variables: (1) brand awareness, (2) brand image, (3) perceived quality, and (4) brand loyalty.